Biodiversity and ecosystem function of tropical forest dung beetles under contrasting logging regimes - Slade, E; Mann, D; Lewis, O (2011)
A key challenge for tropical conservation biologists is to assess how forest management practices affect biodiversity and associated ecosystem functions. Dung beetles (Scarabaeidae: Scarabaeinae) provide an ideal focal guild for such studies. We compared dung beetle assemblages and experimentally assessed rates of dung removal and seed burial in undisturbed forest, low-intensity selectively logged forest under sustainable forest management, and high-intensity logged forest, not under sustainable management in Malaysian Borneo. In total, 7923 individuals from 39 species of dung beetle were collected. There were no significant differences in abundance, biomass or diversity across sites. Species richness was significantly lower in the high-intensity logged sites. Beta diversity was low: of 35 species recorded in undisturbed forest sites, 32 were also captured in low-intensity sites and 29 in high-intensity sites. The environmental and vegetation variables measured had little influence on species composition. An average of 63-99% of dung was removed over 24. h. Mean dung and seed removal were significantly lower in the high-intensity logged sites. Dung removal rates were significantly and positively correlated with dung beetle species richness, but not with dung beetle biomass or abundance. However, the biomass of large-bodied, nocturnal dung beetles was positively correlated with dung removal. In contrast to previous studies, dung beetle biomass and abundance were not correlated with species richness, indicative of density compensation. Overall, dung beetle communities and associated ecosystem functions were robust to low-intensity but not high-intensity selective logging. These differences may be related to changes in the abundance and biomass of particular dung beetle species or guilds rather than community-wide measures of abundance and biomass, highlighting the need to move beyond simplistic biodiversity-ecosystem functioning correlations to understand the functional consequences of habitat modification in high-diversity ecosystems. © 2010 Elsevier Ltd.